Nomenclatural changes in Ochlerini (Hemiptera: Heteroptera: Pentatomidae: Discocephalinae) - Campos, Luiz Alexandre; Roell, Talita (Zootaxa, 2018)
Several nomenclatural problems were found while studying the types of Ochlerini in the Natural History Museum, London. These problems are addressed and corrected: Hemingius Distant, 1899 syn. nov. is removed from the synonymy with Moncus Stål, 1867, and considered a new junior synonym of Ochlerus Spinola, 1837; Ochlerus scaber Walker, 1867 is removed from the synonymy with Ochlerus obscurus Dallas, 1851, and it is proposed as a senior synonym of Ochlerus cotylophorus Breddin, 1910 syn. nov. Herrichella Distant, 1911 is a senior synonym of Alitocoris Sailer, 1950 syn. nov., with the resulting new combinations: Herrichella grandis (Garbelotto & Campos, 2013) comb. nov., Herrichella lateralis (Garbelotto & Campos, 2013) comb. nov., Herrichella ornata (Garbelotto & Campos, 2013) comb. nov., and Herrichella schraderi (Sailer, 1950) comb. nov. A key for the species of Herrichella is also given. Eritrachys antennata (Distant, 1911) comb. nov. is a senior synonym of Eritrachys bituberculata Ruckes, 1959 syn. nov. Phereclus punctatus (Dallas, 1851) is transferred to the genus Lincus Stål, 1867 as Lincus punctatus (Dallas, 1851) comb. nov.